Preface - Tina Uys; Jan Marie Fritz (Clinical Sociology Review)
We are very pleased to bring you Volume 17 of the Clinical Sociology Review (CSR). The first volume of the CSR was published in 1982 and Volume 16 was published in 1998. The original sponsor, the Clinical Sociology Association, decided to expand the scope of the organization and the CSR became part of a journal with a different name. Many colleagues thought it was time to reinvent the original journal. We hope you enjoyed reading the first 16 volumes of the CSR by visiting the Wayne State University website at https://digitalcommons.wayne.edu/csr/ and that you look forward to reading the new issues.